A study of the effect of sports participation on married youth’s fertility intentions - chain mediation based on marital and family functioning - Li Lin; Xinze Li; Cen Cong (Frontiers in Public Health)
IntroductionThis study investigates the impact of sports participation on the fertility intentions of married young adults in China, utilizing data from the 2022 China Family Panel Studies (CFPS). By integrating Self-Determination Theory (SDT) and Family Systems Theory (FST), the study hypothesizes that sports participation enhances fertility intentions through mediation by marital and family functioning.MethodsA sample of 1,087 valid cases was analyzed using probit regression and structural equation modeling.ResultsThe results indicate that each one-unit increase in sports participation is associated with a 0.048 higher probability of intending to have a child. Specifically, Structural equation modeling with 1,000 bootstrapped samples confirms that marital functioning mediates this relationship (indirect effect = 0.023, 13.7% of the total effect; p < 0.10), family functioning mediates more strongly (indirect effect = 0.082, 48.8%; p < 0.01), and the chain mediation through both subsystems accounts for 0.063 (37.5%; p < 0.01).DiscussionThis study underscores the importance of both marital and family subsystems in shaping fertility decisions, suggesting that policies promoting sports participation and family-centered support may effectively enhance fertility intentions among young married individuals.